Internal Assessment in EFL Classrooms: Implementation and Student Perspectives in a Semester-Based System - Khatri, Chitra Bahadur (Journal of Educational Research and Innovation, 2025)
Although educational assessment is frequently equated with summative testing and grading, its scope extends significantly into formative practices that drive students’ learning achievement. However, the implementation and reception of these practices within specific academic contexts require further investigation. This study explores the practices and perspectives regarding internal assessment in EFL classrooms at Mid-West University, Nepal. Employing a mixed-methods research design, data were collected from 60 Bachelor of Education (B.Ed.) students majoring in English Education using closed- and open-ended questionnaires. Quantitative data were analysed using descriptive statistics, while qualitative responses underwent thematic analysis. The findings reveal that internal assessment mechanisms in a semester-based system—specifically attendance, presentations, assignments, fieldwork, and mid-term exams—significantly improve learning outcomes, encourage self-directed study, and provide essential continuous feedback. Despite these benefits, students expressed concerns regarding fairness, systematic inconsistency, and potential teacher bias (halo effects). The study concludes that while internal assessment is pivotal for academic progress, its success in higher education relies on the establishment of clear guidelines and standardized teacher training to ensure equity and fairness.